1993
DOI: 10.1128/iai.61.12.5339-5344.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Brucella abortus ssb and uvrA genes from a genomic library by use of lymphocytes as probes

Abstract: BruceUa abortus proteins from virulent S2308 expressed from a pBluescript II SK-genomic library stimulated peripheral blood mononuclear (PBM) cell proliferation from cattle vaccinated with B. abortus S19. The method described here permits a rapid and directed approach to isolate genes encoding antigens of B. abortus that interact with lymphocytes primed to the living bacterium. The supernatants from the bacterial host JM109 (DE3) were cultured with freshly isolated bovine PBM cells. A total of 300 clones were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…proteins rather than by the LPS 0 antigens. A previous study has also shown that blood lymphocytes from S19-vaccinated cattle exhibit proliferative responses to several recombinant S2308 fusion proteins which contain no S2308 LPS 0 antigens (17). In our study, each of the 22 fractions of S2308 and SRB51 did not contain a single protein but instead contained groups of proteins with similar molecular masses, and certainly only some proteins in each fraction stimulated lymphocyte proliferation.…”
supporting
confidence: 58%
“…proteins rather than by the LPS 0 antigens. A previous study has also shown that blood lymphocytes from S19-vaccinated cattle exhibit proliferative responses to several recombinant S2308 fusion proteins which contain no S2308 LPS 0 antigens (17). In our study, each of the 22 fractions of S2308 and SRB51 did not contain a single protein but instead contained groups of proteins with similar molecular masses, and certainly only some proteins in each fraction stimulated lymphocyte proliferation.…”
supporting
confidence: 58%
“…Three ATG codons are present in frame at nucleotide positions 94, 103, and 109. A putative Shine-Dalgarno sequence (GGAG) occurs 9 bp upstream from the third ATG; an identical ribosome-binding site has been reported to be present 10 bp 5Ј to the B. abortus ssb gene starting codon (46). If one considers the third ATG as the start codon, since its location downstream of the putative Shine-Dalgarno site is adequate, the omp10 ORF codes for a 126-amino-acid polypeptide with a calculated MM of 13,251 Da.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify Brucella components that can stimulate lymphocytes from infected animals, one-and two-dimensional SDS-PAGE followed by cellular immunoblotting has been used (8-10); however, this strategy does not allow one to unambiguously exclude the interference of Brucella LPS chains present in the protein preparations. Another study used lymphocytes as probes to identify recombinant stimulatory Brucella proteins expressed by a genomic library (53). In this study, anion-exchange chromatography was used to purify a 39-kDa protein from brucellergen.…”
Section: Discussionmentioning
confidence: 99%